1988
DOI: 10.1523/jneurosci.08-09-03522.1988
|View full text |Cite
|
Sign up to set email alerts
|

NMDA- and non-NMDA-receptor components of excitatory synaptic potentials recorded from cells in layer V of rat visual cortex

Abstract: The pharmacological properties of excitatory synapses on pyramidal cells in layer V of rat visual cortex were investigated by recording EPSPs intracellularly in tissue slices. The EPSPs were evoked by electrically stimulating cells in layer II/III or axons in white matter. All of the layer V neurons were pyramidal in nature as determined by injections of Lucifer yellow or by electrophysiological criteria. Application of the broadly acting antagonists kynurenic acid and gamma-D-glutamylglycine reversibly antago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
60
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(73 citation statements)
references
References 82 publications
13
60
0
Order By: Relevance
“…Moreover, as expected of a monosynaptic synapse, increasing the extracellular Ca2+ concentration reversed the block caused by the high Mg2+ (Nicholls & Purves, 1970;Berry & Penreath, 1976). We propose that this EPSP recorded in high Mg2+ is monosynaptically evoked, in agreement with the results obtained by Jones & Baughman (1988) (Watkins & Evans, 1981) and CNQX (Honore, Davies, Drejer, Fletcher, Jacobsen, Lodge & Nielsen, 1988) respectively and their voltage dependence when physiological concentrations of Mg2+ are present (Nowak et al 1984;Mayer & Westbrook, 1985). Previous studies have shown that neocortical neurons possess NMDA receptors that can be blocked by APV (Thomson, 1986;Artola & Singer, 1987;Jones & Baughman, 1988;Kimura et al 1989;Sutor & Hablitz, 1989 (Jones & Baughan, 1988) and in the CAI region of the hippocampus (Davies & Collingridge, 1989;Andreasen, Lambert & Jensen, 1989) but differ from those reported in other neocortical regions.…”
Section: Evidence For a Monosynaptic Epspsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, as expected of a monosynaptic synapse, increasing the extracellular Ca2+ concentration reversed the block caused by the high Mg2+ (Nicholls & Purves, 1970;Berry & Penreath, 1976). We propose that this EPSP recorded in high Mg2+ is monosynaptically evoked, in agreement with the results obtained by Jones & Baughman (1988) (Watkins & Evans, 1981) and CNQX (Honore, Davies, Drejer, Fletcher, Jacobsen, Lodge & Nielsen, 1988) respectively and their voltage dependence when physiological concentrations of Mg2+ are present (Nowak et al 1984;Mayer & Westbrook, 1985). Previous studies have shown that neocortical neurons possess NMDA receptors that can be blocked by APV (Thomson, 1986;Artola & Singer, 1987;Jones & Baughman, 1988;Kimura et al 1989;Sutor & Hablitz, 1989 (Jones & Baughan, 1988) and in the CAI region of the hippocampus (Davies & Collingridge, 1989;Andreasen, Lambert & Jensen, 1989) but differ from those reported in other neocortical regions.…”
Section: Evidence For a Monosynaptic Epspsupporting
confidence: 89%
“…At all events, any class of inhibitory neurons provides at best a disynaptic input to pyramidal cells since all the afferents arising from the white matter or from the cortico-cortical axons are excitatory (Peters, 1987). Indeed, in the prelimbic cortex (Audinat et al 1989 and the present study) as in other neocortical regions, the IPSP always followed the EPSP (McCormick et al 1985;Avoli, 1986;Thomson, 1986;Connors et al 1988;Jones & Baughman, 1988).…”
Section: Afferent Pathways To Layer V Pyramidal Cellssupporting
confidence: 68%
See 1 more Smart Citation
“…Dendrites in CA1 stratum radiatum contain the highest density of NMDA receptors in the hippocampus, and the voltage sensitivity of these receptors could help boost temporoammonic inputs (Jones and Baughman, 1988;Mel, 1988). Although we do not rule out the possible role of presynaptic disinhibition of GABAergic interneurons at this point, we first assessed the role of NMDA receptors in circuit integration of afferent inputs by determining the effects of perfusion with the NMDA antagonist AP-5 (50 M) during temporoammonic-Schaffer collateral integration experiments.…”
Section: Circuit Integration: Activation Of Nmda Receptors Gates Tempmentioning
confidence: 99%
“…The increase of the input resistance will therefore counteract the effect of decreased driving force on the EPSP amplitude. Finally, the depolarization of the cell enhances activation of NMDA receptor-mediated 23,35,49,50 and other voltage-dependent conductances, 10,21,31,47 which could amplify the EPSP.…”
Section: Temperature Dependence Of Synaptic Transmissionmentioning
confidence: 99%